Teaching Strategies in Online Reading Classroom: A Case Study - Episiasi; Bambang Sulistyo; Yentri Anggeraini (Universitas Lancang Kuning, 2022)
The Covid 19 pandemic has made people familiar with online activities including teaching and learning. Unlike face-to-face learning, teachers can see and interact directly in the online classroom. It is important to carry out the English teachers` strategies in promoting reading to the learners. This case study aims to determine the strategies of English teachers in English classrooms, especially strategies for improving reading skills. Interviews, observations and questionnaires are used to collect data. The results show that the strategies of reading aloud in virtual meetings, silent reading and downloaded digital storytelling are the most familiar to teachers in English teaching. The most popular platforms are WhatsApp groups and Zoom meetings and the application used by learners are KAMUSKU and google translate.